Interpretation and translation practices in the scientific production of neoconservatism and neoconservative education policies (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2022)
This work presents partial results of an ongoing investigation on the theme of neoconservatism and neoconservative policies in the educational field. It seeks to analyze how the practices of interpretation and translation of the theme are configured in articles published during the decade of 2012 to 2022. The study is based on meta-research assumptions with emphasis on Epistemologies of Education Policies. It surveys articles written by Brazilian and foreign researchers published in journals of national and international scope, followed by the selection of a sample of productions in the field of education policies with a view to categorizing and analyzing the theoretical-epistemological perspectives, epistemological approaches and positions. With the research, it was perceived the mobilization of a significant production of studies on neoconservatism and the efforts undertaken by scientific communities, around the world, in the interpretation/translation of the developments generated by neoconservative policies in education. Different theoretical-epistemological perspectives come into play in this process of analysis, and most studies are based on the Marxist academic tradition and tend to a critical-normative position. Although to a lesser extent, other theories and epistemologies are also evidenced, generating new readings in relation to the events present. This intense movement is based on the affirmation of ethical commitment to the debate of these issues that affect education and require clear and coherent positions of the scientific communities.Keywords: Neoconservatism. Educational policies. Meta-research.